The crisis of citizenship in the Arab world - Meijer, Roel; Butenschøn, Nils A. (Nils August), 1949- (Social, economic, and political studies of the Middle East and Asia, 2017)
The Crisis of Citizenship in the Arab World argues that the present crisis of the Arab world has its origins in the historical, legal and political development of state-citizen relations since the beginning of modern history in the Middle East and North Africa. The anthology covers three main topics. Part I focuses on the crisis of the social pact in different Arab countries as it became manifest during the Arab Uprisings. Part II concentrates on concepts of citizenship in Islamic doctrine, Islamic movements (Muslim Brotherhood and Salafism), secular political movements and Arab thinkers. Part III looks into the practices that support the claims to equal rights as well as the factors that have obstructed full citizen rights, such as patronage and clientelism. Contributors are: Ida Almestad, Claire Beaugrand, Assia Boutaleb, Michaelle Browers, Nils Butenschøn, Anthony Gorman, Raymond Hinnebusch, Engin F. Isin, Rania Maktabi, Roel Meijer, Emin Poljarevic, Ola Rifai, James Sater, Rachel Scott, Jakob Skovgaard-Petersen, Robert Springborg, Stig Stenslie, Morten Valbjørn, Knut S. Vikør and Sami Zemni. For the Introduction, please click here.